BISTRO: the online platform for terminology management. Structuring terminology without entry structures - Streiter, Oliver; Ralli, Natascia; Ties, Isabella; Voltmer, Leonhard (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
BISTRO is an online platform which supports the translation process in various phases. The phases which can be distinguished are the terminologi-cal preparation of the source text, the creation of terminological glossaries and the retrieval of related documents and their terminological elaboration. For this purpose BISTRO hyperlinks a terminology database with bilingual and trilingual corpora. Term tools such as term extraction (TE), term recognition (TR) and keyword-in-context (KWIC) may be applied to the query results, which consist of retrieved terms or corpus segments. BISTRO ’s architecture is open for new tools and contents, providing at the same time the interface for the management of the underlying data structure and the constant update of the terminological data.